Faktor - Faktor yang Mempengaruhi Produktivitas Usaha Budidaya Udang Vaname (Litopenaeus vannamei) Di Kabupaten Pangkep - Kasim, Nur Alam; Wahyuni; Zam, Megawati; Ilham (Jurnal Galung Tropika, 2024)
Vaname shrimp (Litopenaeus vannamei), one of the leading commodities in the fisheries sector in Pangkep district. Vaname shrimp cultivation is done traditionally and intensively. Vannamei shrimp production and productivity fluctuated. Production inputs influence these fluctuations. This research is to analyse the level of production and the factors that affect the productivity of vaname shrimp farming in Pangkep district. Determining of the respondent is this research is done by purposive. The method is descriptive analysis and Cobb-Douglas production function or double log regression. The study research shows that the average production of Vaname shrimp farming in Pangkep district was 3,553.06 kg/cycle, productivity was 1,724.96 kg/ha/cycle with a middle land area of 1.58 ha. Productivity of Vaname shrimp positive influenced by variable of land area, seeds, fertilizer of urea, fertilizer of phonska, feed and labour.